Constituents, Antimicrobial and Antioxidant Activities of Pulicaria gnaphalodes (Vent.) Bioss. Volatile Oil from Iran - Kazemi, M.; Nagafi, G.R.; Azad, A. (Asian Journal of Chemistry, 2013)
The water distilled essential oil of the aerial parts of P. gnaphalodes from Qom area of Iran was analyzed by GC-FID and GC/MS methods. Eighty-eight compounds, accounting for 89 % of the total oil, were indentified. The main components of the oil were myrtenol (13.2 %), citronellol (9.0 %), (E)-nuciferol (5.2%), shiromoll (5.1 %), geraniol (5.1 %) and a-pinene (5.0 %). The oil was rich in regards to oxygenated monoterpenes (48.8 %). The antimicrobial activity of the oil was measured by a disc diffusion method. The oil has shown maximum zone of inhibition against Candida albicans (23 ± 1.2 mm) with a value higher than that of fluconazol (18.0 ± 0.3 mm). The oil antioxidant activities were valued by DPPH assay and b-carotene-linoleic acid assays. The essential oil strongly reduced the concentration of DPPH free radical (36.0 ± 1.3 %), with an efficacy higher than that of trolox (33.0 ± 0.5 %). The oil had high inhibition against BHD standard in b-carotene bleaching test.